Defining Nearly Zero-Energy Buildings (nZEB) for Turkey in terms of Boundary Conditions - Gali Taşçı, Gözde (Proceedings of the international conference of contemporary affairs in architecture and urbanism-ICCAUA, 2023)
The European Union has presented that the building sector is responsible for 36% of greenhouse gas emissions due to energy consumption and 40% of all energy consumption. Within the framework of the EPBD directive followed to reduce fossil energy consumption in EU countries, the commission recommendation in 2016 (2016/1318) is to ensure that by 2020 all new buildings are nZEB. The current directive has further steps. In Turkey, the Regulation on Energy Performance in Buildings follows EPBD. However, the definition of nZEB in Turkey should be reviewed within its own boundaries. There are 5 different climatic regions in Turkey with different architectural characteristics. Therefore, different ways will have to be followed in terms of meeting the heating-cooling needs. This research deals with the boundary conditions that may be encountered while developing the nZEB definition for Turkey and proposes climatic definitions, additionally with a development in sectoral operation in building sector.